Effects of Weight Loss Medications on Cardiometabolic Risk Profiles: A Systematic Review and Network Meta-Analysis - Khera, Rohan (Gastroenterology, 2018)
BACKGROUND & AIMS: We performed a systematic review and network meta-analysis to evaluate the overall and comparative effects of weight-loss medications, approved by the Food and Drug Administration (FDA) for long-term use, on cardiometabolic risk profiles of obese adults. METHODS: We performed a systematic literature review through February 28, 2017 to identify randomized clinical trials of the effects of FDA-approved weight loss medications (orlistat, lorcaserin, naltrexone-bupropion, phentermine-topiramate, and liraglutide), administered to obese adults for 1 year or more, compared with placebo or another active agent. Outcomes of interest included changes in blood glucose (fasting blood glucose [FBG] and hemoglobin A1c [A1c]), cholesterol profile (low-density lipoprotein and high-density lipoproteins [HDL]), blood pressure (systolic/diastolic) and waist circumference (WC). We performed pair-wise and network meta-analyses with outcomes reported as weighted and standardized mean differences. Quality of evidence was rated using GRADE. RESULTS: In a meta-analysis of 28 randomized controlled trials (29018 participants; median body mass index, 36.1kg/m2), we associated weight-loss medications with a modest decrease in FBG (weighted mean difference, 4.0 mg/dL; 95% CI, −4.4 to −3.6) and WC (weighted mean difference, reduction of 3.3 cm; 95% CI, −3.5 to −3.1), without clinically meaningful changes in systolic/diastolic blood pressure or cholesterol profile vs placebo (standardized mean difference below 0.2); effects varied among drugs. Phentermine-topiramate use was associated with a substantial decrease in WC and a modest decrease in FBG, A1c, and blood pressure and had minimal effect on cholesterol. Liraglutide use was associated with a substantial decrease in FBG, A1c, and WC and a minimal effect on blood pressure and cholesterol. Naltrexone-bupropion use was associated with moderate increase in HDL cholesterol but had a minimal effect on FBG and WC. Orlistat use was associated with a decrease in low-density lipoprotein and HDL-cholesterol. No drug improved all cardiometabolic risk factors. CONCLUSIONS: In a systematic review and network meta-analysis, we found FDA-approved weight loss medications to have only modest positive effects on cardiometabolic risk profile. Further research is needed to evaluate the long-term cardio-metabolic benefits of these medications. PROSPERO: CRD42016039486